Apoptotic Caspases Prevent the Induction of Type I Interferons by Mitochondrial DNA - Rongvaux, Anthony; Jackson, Ruaidhrí; Harman, Christian C.D.; Li, Tuo; West, A. Phillip; de Zoete, Marcel R.; Wu, Youtong; Yordy, Brian; Lakhani, Saquib A.; Kuan, Chia-Yi; Taniguchi, Tadatsugu; Shadel, Gerald S.; et al. (Cell, 2014)
The mechanism by which cells undergo death determines whether dying cells trigger inflammatory responses or remain immunologically silent. Mitochondria play a central role in the induction of cell death, as well as in immune signaling pathways. Here, we identify a mechanism by which mitochondria and downstream proapoptotic caspases regulate the activation of antiviral immunity. In the absence of active caspases, mitochondrial outer membrane permeabilization by Bax and Bak results in the expression of type I interferons (IFNs). This induction is mediated by mitochondrial DNA-dependent activation of the cGAS/STING pathway and results in the establishment of a potent state of viral resistance. Our results show that mitochondria have the capacity to simultaneously expose a cell-intrinsic inducer of the IFN response and to inactivate this response in a caspase-dependent manner. This mechanism provides a dual control, which determines whether mitochondria initiate an immunologically silent or a proinflammatory type of cell death. [Display omitted] •Deficiency in proapoptotic caspases induces viral resistance in vivo and in vitro•Mitochondrial permeabilization, combined with caspase inhibition, induces type I IFNs•The cGAS/STING pathway is required for caspase-regulated IFN expression•Mitochondrial DNA mediates the activation of the IFN response During viral infections, mitochondrial events of apoptosis trigger the initiation of a cell intrinsic immune response, mediated by the expression of type I IFNs. Proapoptotic caspases, activated simultaneously by mitochondria, are required to inhibit that response and to maintain apoptosis immunologically silent.